Strengthening a research-rich teaching profession: an Australian study. Issue 3 (3rd July 2021) - White, Simone; Down, Barry; Mills, Martin; Shore, Sue; Woods, Annette
ABSTRACT: This paper reports on the background, context, design, and findings of a collaborative research project designed to develop a future roadmap for strengthening an Australian research-rich and self-improving education system. Building on the BERA-RSA Inquiry into the role of research in the teaching profession in the UK (Furlong, 2013 ), the Australian Teacher Education Association (ATEA), Australian Association for Research in Education (AARE) and Australian Council of Deans of Education (ACDE) initiated a national study across education systems and jurisdictions to identify ideas, issues, challenges and opportunities to strengthen teacher education and education policy development through research. The mixed-method study, inclusive of focus groups and an on-line survey collected data from pre-service teachers, teachers, academics and leaders across schools, universities and education departments. A set of recommendations highlight the need for research literacies to be embedded at all stages of a teachers' career and that the profession would benefit from professional learning strategies where teachers are positioned as both critical and discerning consumers and active producers of research. The importance of teachers being able to respond to data within their own set of contextual factors was a key message.